1992
DOI: 10.1021/np50089a009
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Synthesis of Sesquiterpene Lactones, 14. Syntheses of (-)-Arbusclin D and (+)-4-epi-Arbusclin D: The Stereochemical Assignment of Arbusclin D

Abstract: Efficient syntheses of (-)-arbusclin D and (+)-4-epi-arbusclin D are reported. By these syntheses the C-4 stereochemistry of arbusclin D and the absolute configuration of (-)-arbusclin D have been determined to be a s shown in structure 1. The biological activities, such as cytotoxic activity toward P-388 lymphocytic leukemia, plant growth regulating activity, and antimicrobial activity of compounds 1, 3, 7, 9, 12, and 14 were also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 4 publications
0
29
0
1
Order By: Relevance
“…A large number of pseudoguaianolides, 4,5-secopseudoguaianolides, guaianolides, and 4,5-secoguaianolides have been shown to exhibit biological activities, including antitumoral [23], root-growth and germination inhibitory activities [24][25][26][27], as well as preventive or curative activities against phytopatogenic fungi [24,26]. Shimoma et al [28] reported the regio-and stereoselective synthesis of common synthetic intermediates via kinetic resolution with Lipase PS, (Fig.…”
Section: Herbicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of pseudoguaianolides, 4,5-secopseudoguaianolides, guaianolides, and 4,5-secoguaianolides have been shown to exhibit biological activities, including antitumoral [23], root-growth and germination inhibitory activities [24][25][26][27], as well as preventive or curative activities against phytopatogenic fungi [24,26]. Shimoma et al [28] reported the regio-and stereoselective synthesis of common synthetic intermediates via kinetic resolution with Lipase PS, (Fig.…”
Section: Herbicidesmentioning
confidence: 99%
“…Thus, optically active building block 25, with 5 consecutive chiral centers, was successfully prepared. Ramadas et al [81] studied the lipase Amano PScatalyzed acylation of (±)-2-hydroxy methyl-2,3-dihydrobenzofurans for the stereoselective synthesis of the antifungal compound (-)-(R)-arthrographol (26).…”
Section: Fungicidesmentioning
confidence: 99%
“…201 Five new dihydrooxepine-type elemanolides [(233)+237)] have been found in the aerial parts of Mikunia microptera.6 Two new eudesmane isothiocyanates, ( 263) and ( 264), have been obtained from the marine sponge Acanthella klethra and tested as antimalaria agents.20H. 209 A new keto-acid, chloranthalic acid (265), and the sesquiterpene dimer chloranthadimeric acid acetate (266) have been isolated from Chloranthus japonicus,210 whilst another three dimeric compounds, shizukaol B (267), shizukaol C (268), and shizukaol D (269), have been found in another species of this genus, Chloranthus serratus."' Chromatographic and spectroscopic data of the eight stereoisomers of eudesm-1 I -en-4-01 have been reported.…”
Section: Elemanementioning
confidence: 99%
“…
A total of eleven naturally occurring guaianolides, 1 iP,13-dihydrokauniolide, estafiatin, isodehydrocostuslactone, 2-oxodesoxyligustrin, arborescin, 1 ß,13-dihydroludartin, 8-deoxy-11 ß, 13-dihydrorupicolin B, ludartin, kauniolide, dehydroleucodin, and leucodin, and three related compounds, 1,10-epiarborescin, 8-deoxyrupicolin B, and 3,4-epiludartin, were synthesized through a common cationic intermediate A, which was derived from ( 1151)-1 ß-(mesyloxy)eudesm-3-eno-12,6a-lactone [2] by solvolytic rearrangement.The guaianolides represent one of the largest groups of sesquiterpene lactones with over 500 known naturally occurring compounds (2). Some of them have been shown to possess high antitumor (3-15), antishistosomal (3,16,17), anthelmintic (18), contraceptive (19,20), root-growth stimulatory (3,21,22), root-growth and germination inhibitory activities (3,4,(13)(14)(15)23,24), and preventive or curative activities for crop diseases (4,15). Because of the diverse biological activities of the guaianolides and since they are
…”
mentioning
confidence: 99%
“…The guaianolides represent one of the largest groups of sesquiterpene lactones with over 500 known naturally occurring compounds (2). Some of them have been shown to possess high antitumor (3-15), antishistosomal (3,16,17), anthelmintic (18), contraceptive (19,20), root-growth stimulatory (3,21,22), root-growth and germination inhibitory activities (3,4,(13)(14)(15)23,24), and preventive or curative activities for crop diseases (4,15). Because of the diverse biological activities of the guaianolides and since they are…”
mentioning
confidence: 99%